2022
DOI: 10.15537/smj.2022.43.1.20210694
|View full text |Cite
|
Sign up to set email alerts
|

Impacts and effects of COVID-19 infection in pregnancy

Abstract: Objectives: To explore the trimester wise significance of the primary outcome in pregnant women during coronavirus disease-19 (COVID-19) pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The increase in uterine artery PI values may be useful in predicting the patients to be followed in terms of preeclampsia and FGR risk in pregnant individuals who had COVID‐19. In another study investigating the effects of COVID‐19 infection on pregnancy ( n = 74), it was found that the incidence of fetal growth restriction is higher in pregnant women who have had this infection ( p < 0.001) 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in uterine artery PI values may be useful in predicting the patients to be followed in terms of preeclampsia and FGR risk in pregnant individuals who had COVID‐19. In another study investigating the effects of COVID‐19 infection on pregnancy ( n = 74), it was found that the incidence of fetal growth restriction is higher in pregnant women who have had this infection ( p < 0.001) 20 …”
Section: Discussionmentioning
confidence: 99%
“…In another study investigating the effects of COVID-19 infection on pregnancy (n = 74), it was found that the incidence of fetal growth restriction is higher in pregnant women who have had this infection ( p < 0.001). 20 COVID-19 infection can cause myocarditis. 21,22 It has been…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Wei et al, 12 there is a relationship between COVID‐19 and low birth weight, as in our study. According to Sunder et al, COVID‐19 increases the risk of fetal growth restriction 24 …”
Section: Discussionmentioning
confidence: 99%
“…According to Sunder et al, COVID-19 increases the risk of fetal growth restriction. 24 Khalil et al detected an increase in the incidence of stillbirth during the COVID-19 pandemic. 25 In the study of Mor et al, although it was observed that the stillbirth rate increased in COVID-19 disease, no relationship was found between intrapartum fetal death rate and COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…The complications by trimester of pregnancy were statistically significant for miscarriage where 25%–26% reported in the 1st trimester, 40% in the second, and 0% in the third one. No vertical transmission was observed ( Sunder et al, 2022 ). In the Sultanate of Oman, it was shown that the risk of ICU admission, preterm labor, pre-eclampsia, and emergency lower segment C-section, in addition to thromboembolic complications, are increased in pregnant women with COVID-19.…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%